BNT162b2 vaccine induces antibody release in saliva: a possible role for mucosal viral protection? - Abbass Darwich; Chiara Pozzi; Giulia Fornasa; Michela Lizier; Elena Azzolini; Ilaria Spadoni; Francesco Carli; Antonio Voza; Antonio Desai; Carlo Ferrero; Luca Germagnoli; ICH COVID‐19 Task‐force; et al. (EMBO Molecular Medicine)
Abstract Vaccination against an airborne pathogen is very effective if it induces also the development of mucosal antibodies that can protect against infection. The mRNA‐based vaccine‐encoding SARS‐CoV‐2 full‐length spike protein (BNT162b2, Pfizer/BioNTech) protects also against infection despite being administered systemically. Here, we show that upon vaccination, cognate IgG molecules are also found in the saliva and are more abundant in SARS‐CoV‐2 previously exposed subjects, paralleling the development of plasma IgG. The antibodies titer declines at 3 months from vaccination. We identified a concentration of specific IgG in the plasma above which the relevant IgG can be detected in the saliva. Regarding IgA antibodies, we found only protease‐susceptible IgA1 antibodies in plasma while they were present at very low levels in the saliva over the course of vaccination of SARS‐CoV‐2‐naïve subjects. Thus, in response to BNT162b2 vaccine, plasma IgG can permeate into mucosal sites and participate in viral protection. It is not clear why IgA1 are detected in low amount, they may be proteolytically cleaved.